Corporate law, governance, and sustainability : the public turn in the global socio-ecological transition - Junqueira, Gabriela de Oliveira (2024)
The overlap of financial, economic, ecological, and political crises has pushed the consensus on the need to promote a socio-ecological transformation, or, in short, a green transition. The discontent with the corporate world for its contributions to those crises has taken a central stage, with calls for greater corporate responsibility being articulated under a sustainability imperative. In the context of a new round of debates on the purpose of companies, this thesis examines the turning of corporate law and governance into a site for advancing a new capitalism. More specifically, the research investigates institutional changes occurring under the label of the public turn in corporate law, addressing the following questions: what constitutes the so-called public turn? What are its drivers and the perspectives on it? Which structural features led to targeting corporate law and governance to push for responsible corporate conduct? How does the public turn in corporate law relates to the broader set of actors and norms that shape corporate governance? Guided by critical approaches to the green transition and by political theories of corporate governance, the thesis resorts to different scholarships to examine the current wave of public oriented corporate governance mechanisms from within and from without corporate law. On the one side, the thesis offers a taxonomy of corporate law strategies being employed as well as a rich account on the multiple dimensions assumed by the new tools, placed at the intersection of human rights and environmental protection, corporate social responsibility, and global value chains. On the other, the thesis embeds corporate laws public turn within the unfolding of global capitalism, as the field evolves from corporate law to corporate governance to sustainable corporate governance. The thesis argues that the public turn in corporate law, caught in between the global and the local, enables the investigation of changing roles of states, businesses, and civil society within the political and epistemic terrain of the transition to a more just and sustainable economy.